An Appraisal of the Practice and Procedure of Sulh (Settlement out of Court) an Islamic Law Perspective - Adamu, Abubakar; Ardo, Hamidu (LECTURES: Journal of Islamic and Education Studies, 2025)
Sulh Meaning Amicable Settlement or Conciliation is a Fundamental Mechanism in Islamic Jurisprudence for Resolving disputes outside formal Court Proceedings rooted in the Principle of Justice and Social Harmony. This Appraisal Examines the Legal framework, historical eviction and contemporary application of Sulh in Islamic Law, it explore how Sulh is Structured in the context of different legal schools and compares it with more than Alternatives Dispute Resolution (ADR) Mechanisms highlighting both the Similarities and the features of Islamic Settlement Processes. In Islamic legal Introduction, Sulh is Permissible in matters of Personals disputes, Property Rights, and even some Criminal cases, provided it does not contravene divine injunctions or Public welfare. The appraisal concluded by evaluating the Potential of Sulh in contemporary legal context, advocating for it integration within modern ADR Practices and Proposing reforms to enhance its applicability Particularly in multi-cultural and Pluralistic societies. This Study also highlights the benefit of Sulh in Preventing relationship and promoting Peace making.   It is an Enduring Modern Dispute Resolution in both Muslim and Non-Muslims Communities.